2021
DOI: 10.12968/gasn.2021.19.10.26
|View full text |Cite
|
Sign up to set email alerts
|

Care without sufficient knowledge of people with home enteral tube feeding: a qualitative study

Abstract: Aim: This study aimed to explore family caregivers' experiences with tube feeding at home in Iran. Methods: This qualitative study was conducted with purposefully selected family caregivers who participated in an in-depth, semi-structured, face-to-face interview. Data analysis was performed through content analysis and rigor was investigated. Results: In total, 20 caregivers were interviewed. Two main categories were found in the interview data: ‘abandoned training’ and ‘lack of knowledge of nutrition’. Partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
1
1
0
3
Order By: Relevance
“…The findings reveal that skills training created the opportunity for caregivers to better understand the care measures, knowing in the practice what was evident in our findings in relation to increased security, confidence and motivation of the participants in carrying out the care practices. As well as it corroborates the stimulus to autonomy and empowerment for decision-making, competence development, recognition of difficulties and problems that can arise from care through critical reflection for safe home-based care 31 .…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The findings reveal that skills training created the opportunity for caregivers to better understand the care measures, knowing in the practice what was evident in our findings in relation to increased security, confidence and motivation of the participants in carrying out the care practices. As well as it corroborates the stimulus to autonomy and empowerment for decision-making, competence development, recognition of difficulties and problems that can arise from care through critical reflection for safe home-based care 31 .…”
Section: Discussionsupporting
confidence: 63%
“…Accordingly, a study (30) that explored the experiences of caregivers and family members of patients using HENT identified that the participants felt unprepared, without sufficient training or education and without support from health professionals, without even knowing how to prepare EN or the correct position for feeding and feeding and problems that can arise from care through critical reflection for safe home-based care (31) .…”
Section: Skills Training As An Enabler Of Teaching In Differentmentioning
confidence: 99%
“…También comprueban que estimula la autonomía y el empoderamiento para la toma de decisiones, desarrollo de competencias, reconocimiento de las dificultades y problemas que pueden surgir en el cuidado a través de la reflexión crítica para brindar un cuidado seguro en el domicilio (31) .…”
Section: Discussionunclassified
“…Resultados: participaram 30 cuidadores, observou-se evidência de diferença de conhecimento entre os tempos t1 e t0. A análise da comparação final sobre o aumento do conhecimento entre os grupos CE e TH, por teste t-Student,evidenciou uma diferença estimada 33,98;2,31) e valor de p de 0,46. Conclusão: ocorreu uma maior elevação de conhecimento entre os tempos t1 e t0, quando comparada os tempos t2 e t1 em ambos os grupos.…”
unclassified
“…evidenciou uma diferença estimada 33,98;2,31) e valor de p de 0,46. Conclusão: ocorreu uma maior elevação de conhecimento entre os tempos t1 e t0, quando comparada os tempos t2 e t1 em ambos os grupos.…”
unclassified